Implementation of the SMart-Punakawan Covid-19 (Sebelas Maret-Pendampingan UNtuk mAsyarakat dan KeluargA melaWAN Covid-19) in Surakarta - Eti Poncorini Pamungkasari; Bulan Kakanita Hermasari; Sri Anggarini Parwatiningsih; Sri Mulyani; Hartono Hartono; Lely Tri Pangesti (Journal of Community Empowerment for Health, 2022)
The Covid 19 pandemic cannot be predicted when it will end. In June 2021, there has been very significant increase in new cases. The government has tried to control transmission by launching the 5M propaganda, consists of wearing masks, maintaining distance, washing hands with soap, avoiding crowds and reducing mobility. However, there are still problems existing related to community compliance in preventing the transmission of Covid 19, for example the use of masks and avoiding crowds. The aim of this project is develop and implement health education media related to Five M and Covid-19 vaccination.This project begins with development education media considering cultural wisdom, in order to easily accepted by the community. The term SMart-Punakawan Covid-19 (Sebelas Maret-Pendampingan UNtuk mAsyarakat dan KeluargA melaWAN Covid-19) was chosen to named this media. Punakawan is a puppet character,  the "servant" of the knights but has an important role as an advisor, so it is very suitable to represent health workers. There are several media used to convey the SMart-Punakawan  including videos, banners, brochures and its implemented to the community either face to face and online (youtube, whatsapp group) in order to reach wider community. The effectivity of this project measured quantitatively using instruments to measure knowledge about Five M and Covid-19 vaccination before and after implementation. We use Wilxocon test because the data wasnot normally distributed. As the result, there is significant differences on respondent knowledge before and after implementation (p<0.001). The SMart-Punakawan is effective in improving people’s knowledge related Five M and Covid-19 vaccination. However, further exploration is  still needed to know impact of the SMart-Punakawan in changing people’s behaviour.